PERKEMBANGAN PEMIKIRAN FIQH IMAM SYAFI’I DALAM QAWL QADĪM DAN QAWL JADĪD: Vol 06 Nomer 02 September 2019 - Rohman, Fathur (Irtifaq, 2019)
This article discusses the development of Imam Syafi’i Fiqh in the Qawl Qadīm and Qawl Jadīd. It is known that the basic thoughts of Imam Shafi'i are Al-Qur'an, Al-Sunnah, Ijma’, and Qiyas which are the main assets for him to be able to develop his fiqh thinking as can be understood as Qawl Qadīm and Qawl Jadīd. These two things for Imam Syafi’i are proof that fiqh law will very likely experience changes in accordance with the social, political, geographical, scientific, cultural, and scientific depth of a person who recites that fiqh law which is usually strongly influenced by background in the scientific field. which he fielded. Keywords: Fiqh Thought, Qawl Qadīm and Qawl Jadīd